2018
DOI: 10.1186/s12859-018-2166-6
|View full text |Cite
|
Sign up to set email alerts
|

An automatic method to calculate heart rate from zebrafish larval cardiac videos

Abstract: BackgroundZebrafish is a widely used model organism for studying heart development and cardiac-related pathogenesis. With the ability of surviving without a functional circulation at larval stages, strong genetic similarity between zebrafish and mammals, prolific reproduction and optically transparent embryos, zebrafish is powerful in modeling mammalian cardiac physiology and pathology as well as in large-scale high throughput screening. However, an economical and convenient tool for rapid evaluation of fish c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, using electrocardiographic signals in a zebrafish embryo requires precise positioning of the electrodes to obtain reproducible signals [ 18 ]. Kang et al found outthat counting heartbeats manually was more unreliable as there is a high possibility of biased results due to individual error, which measures the variation between repeated experiments by an individual, and from the crowd error, which measures the variation between different operators, even when the counting was done by trained individuals [ 19 ]. Gaur et al [ 20 ] also reported the manual counting method.…”
Section: Overview Of Embryo Cardiac Rhythm Detectionmentioning
confidence: 99%
“…However, using electrocardiographic signals in a zebrafish embryo requires precise positioning of the electrodes to obtain reproducible signals [ 18 ]. Kang et al found outthat counting heartbeats manually was more unreliable as there is a high possibility of biased results due to individual error, which measures the variation between repeated experiments by an individual, and from the crowd error, which measures the variation between different operators, even when the counting was done by trained individuals [ 19 ]. Gaur et al [ 20 ] also reported the manual counting method.…”
Section: Overview Of Embryo Cardiac Rhythm Detectionmentioning
confidence: 99%
“…The heartbeat rate can be an early sign and a reliable indicator in assessing the severity of Cu toxicity for developing zebrafish with minimal laboratory equipment and resources. This protocol may be easily strengthened by specialised image analysis software for automatic zebrafish heartbeat detection and analysis (Pylatiuk et al, 2014;Kang et al, 2018), reducing time and resources for initial evaluation of Cu toxicity on developing zebrafish. It would be interesting to validate this method in other fish species or environmental pollutants for potential reduction of required resources and experimental animals in pilot experiments for toxicological research.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a range of anatomical, biochemical, and viability indicators are useful in assessing the toxic effect of enhanced concentrations of Cu on developing embryos (Parichy et al, 2009). Heartbeat rate is one of the parameters affected by heavy metals and has the potential to be widely and easily used for toxicological research on developing zebrafish embryos (Kang et al, 2018). It is a reliable method for piloting experimental work required for designing toxicological experiments, such as selecting a potentially toxic agent and its concentration for further research.…”
Section: Introductionmentioning
confidence: 99%
“…Different platforms and software, such as ZebraPace (Zebrafish Precise Algorithm for Cardiac-rhythm Estimation), MicroZebraLab TM (v3.5, ViewPoint, Lyon, France) or DanioVison system (Noldus Information Technology, Netherlands), have been developed to quantify the contractility, heart rate, incidence of arrhythmia, and blood flow in zebrafish embryos/larvae (Parker et al, 2014;Gaur et al, 2018;Kang et al, 2018;Wang et al, 2020).…”
Section: Platform Development To Perform Cardiac Assays In Zebrafish Embryos/larvaementioning
confidence: 99%